Odpowiedzi

Najlepsza Odpowiedź!
2010-03-15T20:46:25+01:00
X/6 - 1/6 = 1 I*6
x-1=6
x=6+1
x=7

3/4(2-3x)=-6 I *4
3(2-3x)=-24
6-9x=-24
-9x=-30
x=10/3

1/5(x-3)=9-x I *5
x-3=45-5x
6x=48
x=8

0,6+x:2=x+1 I *10
6+5x=10x+10
-5x=4
x=-4/5
2010-03-15T20:46:44+01:00
X/6 - 1/6 =1 /*6
x-1=6 /+1
x=7

3/4(2-3x)= -6 /*4
6-9x=-24 /+9x +24
30 = 9x / :9
x = 30/9

1/5(x-3)=9-x /*5
x-3=45-5x /+5x+3
6x=48 / :6
x=8

0,6 + x:2=x+1 /*2
1,2+x=2x+2 / -x-2
-0,8=x
x=-0,8
2010-03-15T20:57:14+01:00
X/6-1/6=1 //*6
x-1=6
x=7

3/4(2-3x)=-6 //*3/4
6/4 - 9/4x = 6 //*4
6-9x=18
-9x=18
x=-2


1/5(x-3)=9-x
1/5x-3/5=9-x //*5
1x+5x=+3-45
6x=-48
x=8

0,6+x:2=x+1 //*10
6+5x=10x+10
-4=5x
x=-4/5